Assessment of Half-Sib Progeny of Candidate Plus Trees and Clonally Propagated Eucalyptus - Dogra, A. S.; Luna, R. K. (Indian Forester, 2006)
A trial of progeny of 12 half-sib families of Candidate Plus Trees (CPTs), 4 sources of clonally propagated planting material, one source of clonal seed orchard seedlings and three unknown seed sources of Eucalyptus hybrid was conducted at Kharkan Research Station, Hoshiarpur (Punjab) to assess growth performance and to evaluate genetic variability. Among all the planting material tested, clone 72 was found to be most promosing followed by clone 274, CSO seedling source of Bhadrachalam and CPT 12. However, all clonal material showed better qualitative characters of axis persistence and straightness. Analysis of variance of data indicated significant difference among clonal planting material and progeny of CPTs for height, dbh, axis persistence and straightness. Genetic analyses showed high heritability estimates for axis persistence and straightness (58%-69%) and low heritability for dbh. The study suggests that CPT 12 may be multiplied by vegetative means after clonal evaluation for future plantation programme. It is further suggested to select plus trees among populations having broad range of variation.